The Influence of High Dietary Energy Sources on Haematological Status and Niacin Treatment of the Rabbits - Ironkwe, M.O.; Oruwari, B.M. (Pakistan Journal of Nutrition, 2011)
Four isonitrogenous diets A-control B-12% palm oil, C-12% groundnut oil and D-33% corn meal were fed to 40 weanling rabbits. The experiment was a Completely Randomized Design (CRD). At the end of the 15th week, blood was collected from 24 of the rabbits through cervical cutting while 16 were treated with niacin for another 8 weeks. The blood was collected to ascertain whether the high dietary energy diets was stressogenic on the rabbits through their blood parameters. The result showed significant (p<0.05) reduction in all the blood parameters except the white blood cells. This tended to indicate that the high dietary treatments (B and D) did impose stress on the rabbits, hence, these blood constituents were altered compared to the control and groundnut oil (A and C) diets. The observed significant (p<0.05) reduction in haemoglobin, packed cell volume and neutrophil production indicate that the oxygen supply to tissues and organs of the rabbits were different and not normal. The significant (p<0.05) pattern was quite the same when the effect of niacin treatment was considered in another analysis. The drug reduced the fat deposits in the coronary arteries and this was reflected in the photomicrograph of the arteries.